Rethinking the digital divide : emerging challenges in new global economy - Mubarak, Farooq (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
ICT and wellbeing are fundamental concerns in information systems science but seem to have an uncertain place in policy and academic groups. Recently, a considerable deal of literature has emerged around the theme of the digital divide; admittedly, weaving an intricate web of hypothetical assumptions about the nature of the problem. In spite of the six decades of critical research that has been conducted on the digital divide, misconceptions about the phenomenon still abound, even within prominent research groups, as witnessed by inconsistent definitions of the term. While the shrinkage in prices of basic ICT equipment has enabled ICT access to masses, the trend of the digital divide has wandered into another direction: a constellation of divides based on skills, type and quality of ICT tools. Simultaneously, a new form of the digital divide related to elderly people is actively raising its head globally, which has been labelled as the grey digital divide in the literature. To remedy these limitations, this research assigns itself a mandate to rethink the phenomenon of the digital divide critically and arrive at a solution. The prime narrative constructed throughout the body of this dissertation centres on the solution to the long awaited problem of the digital divide. To understand this multilevel phenomenon, Finland and Pakistan were taken as reference countries to represent ICT situation in one developed and one developing country. Holistic research design was best suited to address the nature of research questions raised in the research design. The World Bank was a major source of data, in addition to systematic literature review on the digital divide. To bridge further gaps in existent literature, an ongoing literature review which was actively conducted throughout the dissertation writing process continually provided new insights into the topic. Multivariate regression analysis was used to examine large chunks of World Bank data from 191 countries. Results indicate that the digital divide is a much more complex phenomenon than previously understood. Although developed countries have overpassed developing countries in terms of ICT penetration and infrastructure, there are considerable digital divides in developed regions. Results of empirical investigation clarified the quite confused debate between socio-economic indicators and ICT relationships worldwide. Based on analysis of findings and literature, a systematic solution to minimize the digital divide in Pakistan has been proposed. It is premature to conclude that the digital divide can ever be fully bridged. It is an enduring phenomenon that will continue in various forms. However, multilevel efforts can be directed to minimise it as much as possible. Role of ICT in healthcare and social welfare should be a key practical agenda worldwide. Future work on this topic must continue globally and procedures to form a universal assessment mechanism for the digital divide should begin in earnest.

Tietotekniikka ja hyvinvointi ovat keskeisiä kiinnostuksenkohteita tietojärjestelmätieteessä, mutta niiden asema politiikassa ja akateemisissa piireissä vaikuttaa vakiintumattomalta. Viime aikoina merkittävä määrä kirjallisuutta on kasvanut ”digitaalisen jaon” teeman ympärille, mikä on luonut kompleksisia hypoteettisia oletuksia ongelman luonteen ympärille. Huolimatta runsaasta määrästä digitaalista jakoa koskevasta kriittisestä tutkimuksesta, jota on tehty kuuden vuosikymmenen ajan, ilmiöstä on edelleen havaittavissa runsaasti väärinkäsityksiä, jopa merkittävissä tutkimusryhmissä, kuten termin yhtäpitämättömät määritelmät osoittavat. Samaan aikaan kun tietotekniikan hintojen lasku on mahdollistanut tietotekniikan saatavuuden massoille, digitaalisen jaon kehitys on mennyt toiseen suuntaan: on olemassa joukko jakoja, jotka perustuvat tietotekniikkatyökalujen taitoihin, tyyppeihin ja laatuun. Samanaikaisesti digitaalisen jaon uusi muoto ”harmaa digitaalinen jako”, joka liittyy ikäihmisiin, on aktiivisessa kasvussa maailmanlaajuisesti. Nämä rajoitukset ja haasteet silmällä pitäen, tämä tutkimus arvioi kriittisesti ja ratkaisukeskeisesti digitaalisen jaon ilmiötä. Tämä tutkielma keskittyy ensisijaisesti pitkään odotettuun digitaalisen jaon ongelman ratkaisuun. Jotta olisi mahdollista ymmärtää tätä monitasoista ilmiötä, Suomea ja Pakistania käytettiin vertailumaina edustamaan tietotekniikan tilannetta kehittyneessä ja kehittyvässä maassa. Kokonaisvaltainen tutkimus oli sopivin tapa käsitellä tutkimuskysymyksiä. Tutkimus perustuu Maailmanpankin tietoihin sekä systemaattiseen kirjallisuuskatsaukseen digitaalisesta jaosta. Koko väitöskirjaprosessin jatkunut kirjallisuuskatsaus lisäsi jatkuvasti ymmärrystä aiheesta pyrkien täyttämään aukkoja olemassa olevassa kirjallisuudessa sekä antamaan uusia näkemyksiä teemaan liittyen. Monimuuttujaregressioanalyysiä käytettiin tilastollisena menetelmänä Maailmanpankin 191 maata kattavavan suuren tietoaineiston analysoinnissa. Tulokset osoittavat, että digitaalinen jako on paljon monimutkaisempi ilmiö kuin mitä aiemmin on ymmärretty. Vaikka kehittyneet maat ovat kehittyviä maita edellä tietotekniikan levinneisyyden ja infrastruktuurin suhteen, kehittyneillä alueilla on huomattavia digitaalisia jakoja. Empiirisen tutkimuksen tulokset selkeyttivät hyvin sekaantunutta väittelyä yhteiskunnallis-taloudellisten indikaattoreiden sekä tietotekniikan suhteesta maailmanlaajuisesti. Analyysiin ja kirjallisuuteen perustuen ehdotetaan systemaattista ratkaisua minimoimaan digitaalista jakoa Pakistanissa. On ennenaikaista päätellä, että digitaalista jakoa voi koskaan täysin poistaa. Se on ikuinen ilmiö, joka jatkuu eri muodoissaan. Kuitenkin monella tasolla voidaan ryhtyä toimiin sen minimoimiseksi. Tietotekniikan roolin terveydenhoidossa ja sosiaalihuollossa pitäisi olla käytännössä pääosassa keskusteluissa globaalisti. Aihetta koskevan tutkimuksen on syytä jatkua maailmanlaajuisesti. Erityisesti pitäisi aloittaa toimenpiteet, joilla pystyttäisiin arvioimaan digitaalista jakoa kansainvälisesti.